Towards a Capability-based Framework for Reconfiguring Industrial Production Systems. Issue 3 (2015) - Antzoulatos, Nikolas; Rocha, André; Castro, Elkin; de Silva, Lavindra; Santos, Tiago; Ratchev, Svetan; Barata, José
Abstract: Rapidly changing market requirements and shorter product lifecycles demand production systems that are able to cope with frequently changing resources, production-unit capabilities, and product requirements. In this work we provide a framework for such systems, with a focus on identifying some of the key features of a practical language for specifying the production steps, and exploring how and when production-unit capabilities should be built. We motivate the proposed framework with an assembly scenario, which we have implemented on an industrial production system.